Valuable interaction with cognitive remediation and optimal antipsychotics for recovery in schizophrenia (VICTORY-S): study protocol for an interventional, open-label, randomized comparison of combined treatment with cognitive remediation and lurasidone or paliperidone - Kubota, Ryotaro; Ikezawa, Satoru; Oi, Hideki; Oba, Mari S; Izumi, Shoki; Tsuno, Ryoko; Adachi, Leona; Miwa, Mako; Toya, Shunji; Nishizato, Yohei; Haga, Daisuke; Iwane, Tatsuro; et al. (Frontiers in Psychiatry, 2024)
Background Cognitive impairment, a core feature of schizophrenia, is associated with poor outcomes. Pharmacotherapy and psychosocial treatment, when used alone, have inadequate effect sizes for cognitive impairment, leading to recent interest in combination interventions. A previous study examined the additive effect of cognitive remediation on lurasidone in patients with schizophrenia, which was negative. Although improvement in cognitive function was suggested for lurasidone, it was inconclusive because there was no antipsychotic control in the study. To clarify whether lurasidone has a meaningful impact on cognitive function in combination with cognitive remediation, we use paliperidone as a control antipsychotic in this study. We hypothesize that combination with lurasidone will improve cognitive and social function to a greater extent than paliperidone. Methods The valuable interaction with cognitive remediation and optimal antipsychotics for recovery in schizophrenia study is a multicenter, interventional, open-label, rater-blind, randomized comparison study, comparing the effect of lurasidone plus cognitive remediation with that of paliperidone plus cognitive remediation in patients with schizophrenia. The Neuropsychological Educational Approach to Remediation (NEAR) is used for cognitive remediation. Eligible patients will be randomized 1:1 to receive lurasidone or paliperidone combined with NEAR (6 weeks antipsychotic alone followed by 24 weeks combination antipsychotic plus NEAR). The primary endpoint is the change from baseline in the tablet-based Brief Assessment of Cognition in Schizophrenia composite T-score at the end of the NEAR combination treatment period. Secondary endpoints will include change from baseline in social function, schizophrenia symptoms, and quality of life at the end of the NEAR combination treatment period. Furthermore, change from baseline to the end of the pharmacotherapy period and change from the end of the pharmacotherapy period to the end of the NEAR combination treatment period will be assessed for all endpoints. Safety will also be evaluated. Discussion Achievement of adequate cognitive function is central to supporting social function, which is a key treatment goal for patients with schizophrenia. We think this study will fill in the gaps of the previous study and provide useful information regarding treatment decisions for patients with schizophrenia. Clinical trial registration Japan Registry of Clinical Trials ID, jRCTs031200338.